Growth and yield of Hevea brasiliensis: Effect of juvenility of source bush nurseries - Gireesh T; Mercykutty V.C; Mydin K.K (In: Advances and Challenges in Plant Breeding, Biotechnology and Conservation. (Eds. R.B. Smitha; R. Prakashkumar; N.S. Pradeep; K.V. Mohanan and P.V. Madhusoodanan). Malabar Botanical Garden and Institute for Plant Sciences, Kozhikode, India, pp.108-113.)
Natural rubber tree, Hevea brasiliensis (Willd. ex. A. Juss.) Mull. Arg. is being propagated predominantly by asexual methods through patch budding. However, trees exhibit intra-clonal variation in growth and yield which reduced the informity of plantations. Commercially, buds were collected from budwood sticks regenerated every year from the same source bush nurseries. The age of source nurseries may vary from one to 20 years. Present study examines the effect of age and juvenility of buds from six source bush nurseries and mature trees on growth and yield of the most popular clone RRII 105. Bud patches were collected from healthy regenerated budwood aged one year, four year and 20 year old budwood nurseries and directly from 10 year old mature trees. These buds were grafted onto healthy stock seedlings raised in the sursery. The resultant plants were evaluated in a field trial during 2006 to 2014 following standard field practices. Girth of trees in the seven treatments varied during early growth phase. However, in the seventh and eighth year after planting, except the plants raised directly from 10 year old trees, growth of trees did not show any statistically significant difference. Trees raised from mature trees (34.0 cm) compared to those from regenerated budwood nurseries aged one year, four year and 20 years (girth ranged from 40.0 to 46.3 cm). The results indicated that trees originated from all rejuvenated bud sources viz., one, four and 20 years old budwood stocks registered significantly higher rubber yield (ranging from 31.0 to 37.0 gram/tree/tapping). However, trees originated from buds of mature trees registered significantly (p<0.05) inferior growth, tappability (8.0;) and dry rubber yield (28.0 grams per tree per tapping) compared to other treatments. Moreover, buds of mature tree branches recorded higher intraclonal variation in girth than that of trees raised from budwood nurseries. Results of this study demonstrate that the age of budwood sources ranging from one to twenty years does not appear to have any significant role in determining intraclonal variability in growth and yield of rubber and strongly suggest avoiding use of buds directly from mature trees for commercial propagation.
Source Year: 2016
Keywords: Age of budwood; Budding; Hevea brasiliensis; Juvenility; Propagation; Source bush nurseries